2020
DOI: 10.1002/dc.24389
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric neuroblastic tumors: A critical evaluation of cytomorphological features for risk stratification on aspiration cytology

Abstract: Background Neuroblastic tumor (NT) is the most common extracranial solid tumor of childhood with variable outcome which again depends on risk stratification related to distinct biology of the tumor. The use of fine‐needle aspiration (FNA) material for evaluation of cytomorphological parameters and risk stratification in NTs using cytology prognostic score (PS) is limited in routine practice. Methods We reviewed 38 FNA cytology cases diagnosed as pediatric small round cell tumor between time period June 2017 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Furthermore, it is conceivable that GATA2 and GATA3 play a fundamental role in the genesis of neuroblastoma, given their roles in normal sympathoadrenal development. Consistent with this hypothesis, GATA3 was reported to be a first-line immunohistochemical marker to facilitate the pathological diagnosis of neuroblastic tumors [29]. Gata3 cis-regulatory studies using transgenic reporter mouse assays have revealed that even a 662-kb mouse Gata3 YAC containing 451-kb and 211-kb of 5′ and 3′ flanking Gata3 cis-regulatory studies using transgenic reporter mouse assays have revealed that even a 662-kb mouse Gata3 YAC containing 451-kb and 211-kb of 5 and 3 flanking sequences, respectively, was missing the regulatory element(s) that confer expression in sympathoadrenal system organs [30].…”
Section: Neuroblastomas and Gata Factorsmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, it is conceivable that GATA2 and GATA3 play a fundamental role in the genesis of neuroblastoma, given their roles in normal sympathoadrenal development. Consistent with this hypothesis, GATA3 was reported to be a first-line immunohistochemical marker to facilitate the pathological diagnosis of neuroblastic tumors [29]. Gata3 cis-regulatory studies using transgenic reporter mouse assays have revealed that even a 662-kb mouse Gata3 YAC containing 451-kb and 211-kb of 5′ and 3′ flanking Gata3 cis-regulatory studies using transgenic reporter mouse assays have revealed that even a 662-kb mouse Gata3 YAC containing 451-kb and 211-kb of 5 and 3 flanking sequences, respectively, was missing the regulatory element(s) that confer expression in sympathoadrenal system organs [30].…”
Section: Neuroblastomas and Gata Factorsmentioning
confidence: 58%
“…Furthermore, it is conceivable that GATA2 and GATA3 play a fundamental role in the genesis of neuroblastoma, given their roles in normal sympathoadrenal development. Consistent with this hypothesis, GATA3 was reported to be a first-line immunohistochemical marker to facilitate the pathological diagnosis of neuroblastic tumors [29].…”
Section: Neuroblastomas and Gata Factorsmentioning
confidence: 60%
“…Campagna et al (14) concluded that FNAB multi-stitch sampling is su cient for complete diagnosis and can replace OIB. To minimize misdiagnosis, the combination of pathology immunohistochemistry and molecular biology diagnosis is recommended to identify pNT and the rest of SRCT (15)(16)(17). Unfortunately, none of the nine cases in group B underwent further molecular biology diagnosis due to limitations of current technology.…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, they seem similar to other "small round blue cell" neoplasms. 1,27 FNA smears are hypercellular, and composed of nested cells with high nuclear-to-cytoplasmic ratios, scant cytoplasm, and finely granular chromatin. Homer Wright rosettes, with acinar arrangements of tumor cells around fibrillary neuropil material, are occasionally identified.…”
Section: Fine Needle Aspiration Of Noncortical Adrenal Lesionsmentioning
confidence: 99%